2022
DOI: 10.3390/vaccines10050801
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Impairment of the Immune Response to the Moderna-1273 mRNA Vaccine by Mycophenolate Mofetil in Patients with Rheumatic and Autoimmune Liver Diseases

Abstract: The purpose of this study was to evaluate the efficacy and safety of the Moderna-1273 mRNA vaccine for SARS-CoV-2 in patients with immune-mediated diseases under different treatments. Anti-trimeric spike protein antibodies were tested in 287 patients with rheumatic or autoimmune diseases (10% receiving mycophenolate mofetil, 15% low-dose glucocorticoids, 21% methotrexate, and 58% biologic/targeted synthetic drugs) at baseline and in 219 (76%) 4 weeks after the second Moderna-1273 mRNA vaccine dose. Family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…Previous studies have revealed that it impacts the effects of SARS-CoV-2 vaccination, including primary series and mRNA-based vaccine booster schemes. The seroconversion rate and anti-SARS-CoV-2 IgG levels decreased in patients with ARDs receiving mycophenolate mofetil in a dose-dependent manner, especially for a daily dose of >1 gm per day [ 21 ]. The impairment of humoral immunogenicity after vaccination in mycophenolate mofetil users can be attributed to the inhibition of B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that it impacts the effects of SARS-CoV-2 vaccination, including primary series and mRNA-based vaccine booster schemes. The seroconversion rate and anti-SARS-CoV-2 IgG levels decreased in patients with ARDs receiving mycophenolate mofetil in a dose-dependent manner, especially for a daily dose of >1 gm per day [ 21 ]. The impairment of humoral immunogenicity after vaccination in mycophenolate mofetil users can be attributed to the inhibition of B cells.…”
Section: Discussionmentioning
confidence: 99%
“…This patient did not show any significant increase in T-cell markers, which was correlated with the clinical progression of COVID-19. While tacrolimus is not associated with severe disease or increased risk of death in COVID-19 patients (Yin et al, 2021), mycophenolate can cause T-cell depletion and impairment of immune response to SARS-CoV-2 (De Santis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…MMF treatment has been shown to significantly reduce seroconversion rates (69% in MMF group vs. 100% in healthy controls, p < 0.001) and antibody titres in response to the Moderna COVID-19 (mRNA1273) vaccine, with a notable dose-dependent effect. This effect was most pronounced in patients receiving over 1 g daily, leading to both reduced neutralising activity and impaired cytotoxic cellular response [ 36 ]. A similar dose-dependent impact on humoral immune response was observed in another study [ 37 ].…”
Section: Conventional Synthetic Disease-modifying Antirheumatic Drugs...mentioning
confidence: 99%